2015
DOI: 10.1126/science.aac6383
|View full text |Cite
|
Sign up to set email alerts
|

Slip pulse and resonance of the Kathmandu basin during the 2015 Gorkha earthquake, Nepal

Abstract: Movie S1Correction: In table S1, the displacement at station SNDL was reported erroneously. The correct displacement is: east, 0.047 ±0.002 m; north, -0.223 ±0.003 m; vertical, 0.003 ±0.003 m. The PDF has been corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
263
2
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(305 citation statements)
references
References 34 publications
25
263
2
2
Order By: Relevance
“…The low-to-high gradient in the displacement of the aftershock is larger than the main shock suggesting there is a slip concentration at depth. Most of the displacement from the M w 7.3 aftershock occurs near the eastern end of the displacement from the main rupture suggesting it may have been triggered by a Coulomb stress concentration from the main shock [Galetzka et al, 2015].…”
Section: 1002/2015gl065385mentioning
confidence: 99%
See 2 more Smart Citations
“…The low-to-high gradient in the displacement of the aftershock is larger than the main shock suggesting there is a slip concentration at depth. Most of the displacement from the M w 7.3 aftershock occurs near the eastern end of the displacement from the main rupture suggesting it may have been triggered by a Coulomb stress concentration from the main shock [Galetzka et al, 2015].…”
Section: 1002/2015gl065385mentioning
confidence: 99%
“…This manuscript describes the new data and processing methods and more importantly refers to a web site where we present line-of-sight (LOS) data files for each track and frame described here for use in modeling studies [e.g., Wang and Fialko, 2015;Galetzka et al, 2015]. We will continue to provide postseismic LOS data as they become available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rupture propagated eastwards, impacting areas up to ∼ 140 km from the epicenter, with additional large aftershocks concentrated near the eastern end of the mainshock rupture plane Galetzka et al, 2015). A rapid appraisal of the first available imagery suggested that landsliding occurred in an E-W swath located north of the Kathmandu Valley, covering a large proportion of western and central Nepal (∼ 12 000 km 2 ).…”
Section: Initial Landslide Identification Effortsmentioning
confidence: 99%
“…However, significant variations in the details of the rupture process, ranging from linearly distributed high-frequency sources with constant rupture velocity Meng et al 2016), to multistage rupture , and depth dependent variation in rupture velocity ) have been reported. Joint inversion of teleseismic waves, strong ground motion data, high-rate and static GPS data and SAR imagery (Galetzka et al 2015;Grandin et al 2015) pointed to a simple unilateral rupture with steady rupture velocity. The downdip limit of the rupture has been conjectured to coincide with the junction between the frontal flat and deeper steeply dipping ramp on the MHT.…”
Section: Introductionmentioning
confidence: 99%